Enhanced Degradation of Waste Activated Sludge in Microbial Electrolysis Cell by Ultrasonic Treatment - Hu, Kai; Chen, Wei; Jia, Shuo-qiu; Wang, Wei; Han, Feng (Frontiers in Microbiology, 2019)
This study investigates the feasibility of ultrasonic pretreatment for improving treatment efficiency of waste activated sludge in microbial electrolysis cell (MEC). Results showed that at applied voltage of 0.5 V, biogas production and cathodic hydrogen recovery enhanced 3.68-fold and 2.56-fold, respectively. Due to the transformation of soluble COD accelerated by the pretreatment, the removal rates of suspended solids and volatile suspended solids were significantly enhanced by 1.38-fold and 1.48-fold, respectively. Various kinds of organics, including VFAs (volatile fatty acids), proteins and carbohydrates, could be utilized in sequence. The primary biodegradable substance in MEC was hydrophilic fraction from sludge organics and the pretreatment effectively resulted in an elevated concentration of this fraction. The 16S rRNA pyrosequencing analysis demonstrated multiple syntrophic interactions between fermentative bacteria, exoelectrogenes, and methanogenic archaea in MEC for waste activated sludge.